Thermophysical Properties of Copper – Carbon Fibre Composite - Sebo, Pavol; Stefanik, Pavol (Communications - Scientific letters of the University of Zilina, 2004)
In this paper two main properties of copper matrix – carbon fibre composite from the point of view of using it in electronics as a material able to dissipate the heat are presented. Thermal expansion and thermal conductivity of the composite can be changed in dependence on volume amount of fibres in composite, their geometrical arrangement and on the properties of carbon fibres. Propagation of heat across the composite was measured. Results are in good agreement with those obtained by finite elements method calculation.